Pragmatyzm dzisiaj (ze szczególnym uwzględnieniem propozycji Johna Deweya) a jego korzenie antyczne - Chudoba, Ewa (Kultura-Społeczeństwo-Edukacja, 2015)
The author of the article poses the following question: Why would we find Dewey's classic pragmatism interesting and is it true that everything that is really important can be found in the works of his followers: Rorty and Shuterman. The author emphasizes that in her narrative she is mostly  interested in more primal Dewey whose philosophical thoughts, naturalistic empiricism, as he himself called his philosophy, as well as the aesthetic conc ept s are not subject to frequent debates in our coun try She indicates that there are certain abuses in the interpretation of Dewey's philosophy. On e of them is, for example, treating Dewey as a leftist philosopher who has not had much to offer when it come s to the approach to tradition and history. The author emphasizes that although Dewey's point of view was very far from being right-wing or far from accept ing nationalism, he is not a left-wing thinker. Dewey is a philosopher who remains extremely attached to tradition and he believes that knowledge about history is crucial to understand philosophy and culture. The author specifically refers to emphasize that Dewey reminds us of what full of life and contemporary art really is. It stems from the rhythm and needs of social life and it expresses beliefs of a given community or society.